Review article: sarcopenia in cirrhosis – aetiology, implications and potential therapeutic interventions. Issue 7 (5th February 2016) - Sinclair, M.; Gow, P. J.; Grossmann, M.; Angus, P. W.
Summary: Background: Sarcopenia (loss of muscle mass) is common in cirrhosis and is associated with poor outcomes. Current teaching recommends the use of protein supplementation and exercise, however, this fails to address many other factors which contribute to muscle loss in this setting. Aims: To summarise existing knowledge regarding the aetiology of sarcopenia in cirrhosis, diagnostic modalities and the clinical significance of this condition. In addition to discuss recent research findings that may allow the development of more effective treatments. Methods: We conducted a Medline and PubMed search using the search terms 'sarcopenia', 'muscle', 'body composition', 'cirrhosis', 'liver' and 'malnutrition' from inception to October 2015. Results: Cirrhotic patients with sarcopenia have reduced survival, experience increased rates of infection and have worse outcomes following liver transplantation. The aetiology of this condition is more complex than simple protein and calorie malnutrition. Cirrhosis also results in depleted glycogen stores and metabolic alterations that cause excessive protein catabolism, increased activation of the ubiquitin–proteasome pathway and inappropriate muscle autophagy. Satellite cell differentiation and proliferation is also reduced due to a combination of elevated myostatin levels, reduced IGF‐1 and hypogonadism. Although there is some evidence supporting the use of late evening snacks, branched chain amino acid supplementation and high protein/high calorie diets, well designed clinical trials addressing the effects of treatment on body composition in cirrhosis are lacking. Conclusion: Sarcopenia in cirrhosis has a complex pathogenesis and simple dietary interventions are insufficient. Improved understanding of the multiple mechanisms involved should allow the development of more effective therapies, which target the specific underlying metabolic derangements.